How to manage people fast, effective management skills that really get results - Armstrong, Michael (London; New York, NY Kogan Page, 2022)
"This fully updated 5th edition now features even more practical exercises, useful templates, and top tips, alongside advice on managing virtual teams, enhancing employee engagement and managing conflict. Essential reading for anyone who wants to get the best from their teams, How to Manage People distils the essence of good management into one handy, easy-to-use book." --
Managing people -- Leading, motivating and engaging people -- Organizing people -- Managing performance --Approaches to people management -- Handling people problems and issues
Includes bibliographical references
Keywords: Management -- Handbooks, manuals, etc; Leadership -- Handbooks, manuals, etc